Criteria for efficient prevention of dissemination and successful eradication of Erwinia amylovora (the cause of fire blight) in Aragon, Spain - Palacio-Bielsa, Ana; López-Quílez, Antonio; Llorente, Isidre; Ruz, Lidia; López, María M.; Cambra, Miguel A. (2017)
Erwinia amylovora was detected on pome fruits in the Aragon region (North-Eastern Spain), in a ca. 5 km radius area located in the mid Jalon river (mid Ebro Valley) in the province of Zaragoza, during 2000-2003. Eight years have now passed since this pathogen was last detected, without new infections being reported in the same area. The bases for surveys and rapid eradication performed have been analyzed in detail to understand the reasons for the success in removing fireblight. The results demonstrate that intensive surveillance, risk assessment, plant analyses using accurate identification methods, and, especially, rapid total or selective eradication of infected trees in the plots have been very effective in preventing the generalized spread of fireblight and in delaying economic losses associated with this disease. Eradication and compensation to growers, estimated to cost approx. (sic) 467,000, were clearly counterbalanced by the economic value of apple and pear production in the 2000-2003 period (approx. (sic) 368 million). Fire blight risk-assessment, using the MARYBLYT system, showed that climatic conditions in the studied area were favourable to infections during the analyzed period (1997-2006). Molecular characterization of E. amylovora strains had revealed their homogeneity, suggesting that these fire blight episodes could have been caused by just one inoculum source, supporting the hypothesis that there was a unique introduction of E. amylovora in the studied area. Spatial spread of E. amylovora to trees was analyzed within six orchards, indicating an aggregated distribution model. This Spanish experience demonstrates the success of scientifically-based prevention methods that lead to the deployment of a fast and strict containment strategy, useful for other Mediterranean areas.